SOSIALISASI, PENYULUHAN, DAN PELATIHAN PEMBUATAN JAMU PENINGKAT IMUNITAS TUBUH DI DESA LEDUG KABUPATEN BANYUMAS - Arinda Nur Cahyani; Iva Rinia Dewi; Septiana Liaturrohmah; Anisa A (Jurnal Bakti untuk Negeri, 2022)
The most effective thing in preventing the spread of COVID-19 is to increase our body's resistance from within by drinking herbs or traditional ingredients that have been trusted from ancient times. This is not a mere superstition or belief, in fact this has been done since the time of the ancestors. Maintaining health must start from the inside first. And it all starts from our stomach. The purpose of this Community Service is to provide counseling and training on how to make herbal ingredients or herbal drinks in accordance with pharmacognosy theory and ingredients originating from the Ministry of Health. The method used is lectures and discussions to provide an understanding of how to make herbal ingredients correctly as well as simulations and demonstrations by providing skills about making and storing herbal ingredients. Community service can be carried out with permission from the village with 1 counseling activity and skills provision. Counseling on the socialization of herbal ingredients from the Ministry of Health which was presented using LCD media and pamphlets and training on making herbal or herbal drinks were carried out by direct practice.